Prediction of skin dose in low‐kV intraoperative radiotherapy using machine learning models trained on results of in vivo dosimetry. Issue 3 (25th January 2019) - Avanzo, Michele; Pirrone, Giovanni; Mileto, Mario; Massarut, Samuele; Stancanello, Joseph; Baradaran‐Ghahfarokhi, Milad; Rink, Alexandra; Barresi, Loredana; Vinante, Lorenzo; Piccoli, Erica; Trovo, Marco; El Naqa, Issam; et al.
Abstract : Purpose: The purpose of this study was to implement a machine learning model to predict skin dose from targeted intraoperative (TARGIT) treatment resulting in timely adoption of strategies to limit excessive skin dose. Methods: A total of 283 patients affected by invasive breast carcinoma underwent TARGIT with a prescribed dose of 6 Gy at 1 cm, after lumpectomy. Radiochromic films were used to measure the dose to the skin for each patient. Univariate statistical analysis was performed to identify correlation of physical and patient variables with measured dose. After feature selection of predictors of in vivo skin dose, machine learning models stepwise linear regression (SLR), support vector regression (SVR), ensemble with bagging or boosting, and feed forward neural networks were trained on results of in vivo dosimetry to derive models to predict skin dose. Models were evaluated by tenfold cross validation and ranked according to root mean square error (RMSE) and adjusted correlation coefficient of true vs predicted values (adj‐R 2 ). Results: The predictors correlated with in vivo dosimetry were the distance of skin from source, depth‐dose in water at depth of the applicator in the breast, use of a replacement source, and irradiation time. The best performing model was SVR, which scored RMSE and adj‐R 2, equal to 0.746 [95% confidence intervals (CI), 95% CI 0.737, 0.756] and 0.481 (95% CI 0.468, 0.494), respectively, on the tenfold cross validation. Conclusion: The model trained on results of in vivo dosimetry can be used to predict skin dose during setup of patient for TARGIT and this allows for timely adoption of strategies to prevent of excessive skin dose.